The effects of color and neutral density filters on dynamic accommodation in individuals with mild traumatic brain injury - Almutairi, Nawaf M.; Hayes, John; Tai, Yu-Chi; Alfaifi, Khawlah; Alnawmasi, Mohammed M.; Alanazi, Muteb K.; Alenezi, Bandar M.; Aldakhil, Sulaiman; Liu, Chunming (Frontiers in Neuroscience, 2025)
IntroductionVisual symptoms related to accommodation are frequently reported after mild traumatic brain injury (mTBI), yet the effect of spectral and luminance-altering filters on dynamic accommodative performance remains unclear. This study objectively measured dynamic accommodation in individuals with mTBI and healthy controls under various filter conditions to determine if visual performance could be improved.MethodsThirty participants with a medically diagnosed history of mTBI (age range 18–33 years) and 54 healthy controls (age range 21–30 years) completed monocular dynamic accommodation testing under three randomized viewing conditions: baseline with no filter (NF), a subjectively selected color filter (CF), and a luminance-matched neutral density filter (ND). Accommodation and disaccommodation responses to 5.00 D step stimuli were continuously recorded at 50 Hz using the PowerRef 3 photorefractor. First-order response parameters were extracted, such as peak velocity, response amplitude, latency, and response time. A mixed linear model was used to assess group, filter, and interaction effects.ResultsAt baseline (NF), the mTBI group showed significantly reduced accommodation peak velocity (mean difference = −1.68 D/sec) and response amplitude (mean difference = 0.55 D) compared to controls (P < 0.05). CFs did not significantly alter any response parameters in either group. In contrast, ND filters significantly increased accommodation peak velocity (mean difference = +1.77 D/sec) and amplitude (mean difference = 0.67 D) in the mTBI group (P < 0.001). Latency and response time remained stable across all conditions and groups.DiscussionUnder baseline circumstances, especially in speed and magnitude of response, participants with mTBI showed apparent deficits in dynamic accommodation. These findings indicate that, rather than spectral filtering, brightness modulation via ND filters can significantly enhance accommodative performance in individuals with mTBI. This suggests ND filters may serve as a viable clinical intervention for improving accommodative dynamics in this population.